Binding of a fibrinogen mimetic stabilizes integrin αIIbβ3's open conformation - Hantgan, Roy R. (Cold Spring Harbor Laboratory Press, 2001)
The platelet integrin αIIbβ3 is representative of a class of heterodimeric receptors that upon activation bind extracellular macromolecular ligands and form signaling clusters. This study examined how occupancy of αIIbβ3's fibrinogen binding site affected the receptor's solution structure and stability. Eptifibatide, an integrin antagonist developed to treat cardiovascular disease, served as a high-affinity, monovalent model ligand with fibrinogen-like selectivity for αIIbβ3. Eptifibatide binding promptly and reversibly perturbed the conformation of the αIIbβ3 complex. Ligand-specific decreases in its diffusion and sedimentation coefficient were observed at near-stoichiometric eptifibatide concentrations, in contrast to the receptor-perturbing effects of RGD ligands that we previously observed only at a 70-fold molar excess. Eptifibatide promoted αIIbβ3 dimerization 10-fold more effectively than less selective RGD ligands, as determined by sedimentation equilibrium. Eptifibatide-bound integrin receptors displayed an ectodomain separation and enhanced assembly of dimers and larger oligomers linked through their stalk regions, as seen by transmission electron microscopy. Ligation with eptifibatide protected αIIbβ3 from SDS-induced subunit dissociation, an effect on electrophoretic mobility not seen with RGD ligands. Despite its distinct cleft, the open conformer resisted guanidine unfolding as effectively as the ligand-free integrin. Thus, we provide the first demonstration that binding a monovalent ligand to αIIbβ3's extracellular fibrinogen-recognition site stabilizes the receptor's open conformation and enhances self-association through its distant transmembrane and/or cytoplasmic domains. By showing how eptifibatide and RGD peptides, ligands with distinct binding sites, each affects αIIbβ3's conformation, our findings provide new mechanistic insights into ligand-linked integrin activation, clustering and signaling.